Tracheal Cuff Pressure Changes and Associated Factors in Children who underwent Tonsillectomy at Shafa Polyclinic of Zanjan in the 1399-1400 period - Hashem Molaei; Mitra Hojat Ansari; Mohammad Reza Dinmohammadi; Somayeh Abdollahi Sabet (Zanjan University of Medical Sciences and Health Services, 2023)
Background: Endotracheal intubation is a common procedure during tonsillectomy in children, and tracheal tube cuff pressure is subjected to fluctuation during this surgery due to changes in the position of the head and neck. Unusual changes in the tracheal cuff pressure can cause damage to the airway mucosa, tracheal mucosa ischemia, tracheal stenosis, and pulmonary aspiration. Objectives: The present study was conducted to investigate tracheal tube cuff pressure changes and associated factors during tonsillectomy surgery in children. Methods: This cross-sectional study was conducted on 106 children, 3-8 years of age. In this study, the ideal tracheal tube cuff pressure was designated to be 18 cmH2O and measured at four stages phases: after tracheal intubation, after changing the position of the head and neck, 15 minutes after intubation, and before extubation. The data was analysed using SPSS statistics version 26. Frequency (percentage), and mean (standard deviation), as well as Wilcoxon, Friedman, linear regression, and Wald chi-square tests were used for data analysis. Results: The means (standard deviations) of the cuff pressure following after intubation, after subsequent to changing the position of the head and neck, 15 minutes after intubation, and prior to before extubation were 26.69 (6.10), 29.07 (8.39), 29.91 (5.77), and 24.12 (4.72), respectively. The baseline cuff pressure had no statistically significant relationship with age, gender, tube size, BMI, and cuff pressure changes at the 15th minute (P>0.05). The two variables of, gender and tube size, but not age and BMI (P>0.05), were significantly correlated with cuff pressure change prior to extubation compared with baseline line cuff pressure (P<0.05), but eithr age or BMI werenot significantly related to the change in cuff pressure prior to extubation compared with baseline cuff pressure (P>0.05). Conclusion: Tracheal tube cuff pressure during tonsillectomy in children can increase due to the change of head and neck position, making monitoring of these changes necessary in patients undergoing tonsillectomy.